Wide-Field Pixel Super-Resolution Colour Lensfree Microscope for Digital Pathology - Zeng, Guang; He, Jiahui; Qin, Wenjian (Frontiers in Oncology, 2021)
Whole slide imaging (WSI) enables scanning entire stained-glass slides with high resolution into digital images for the tissue morphology/molecular pathology assessment and analysis, which has increased in adoption for both clinical and research applications. As an alternative to conventional optical microscopy, lensfree holography imaging which offers high-resolution and wide field of view (FOV) with digital focus, has been widely used in various biomedical imaging. However, accurate colour holographic imaging with super-resolution reconstruction has remained great challenge due to its coherent characteristic. In this work, we propose a wide-field pixel super-resolution colour lensfree microscopy by performing wavelength scanning pixel super-resolution and phase retrieval simultaneously on the three channels of R, G, and B respectively. High spatial resolution R, G, and B information is reconstructed by converting into YUV space for average filter enhancement, which not only eliminates the common rainbow artifacts of holographic colour reconstruction, but also maintains the high-resolution details collected under different colour illumination. We conducted experiments on reconstruction of a USAF1951, stained lotus root and red bone marrow smear for performance evaluation of the spatial resolution and colour reconstruction with an imaging FOV >40mm2.